Real-world use of orphan medicinal products (OMPs) in rare disease (RD) patients: A population-based registry study - Mazzucato, Monica; Minichiello, Cinzia; Vianello, Andrea; Visonà dalla Pozza, Laura; Toto, Ema; Facchin, Paola (Frontiers in Pharmacology, 2022)
Background: Despite calls for the use of real-world data, the rare diseases (RD) treatment landscape suffers from a scarcity of data referred to orphan medicinal products (OMP) use at population level. Objectives: We aim to describe the characteristics and patterns of utilization of OMP in a sizable group of RD patients globally monitored by an area-based rare diseases registry located in the Veneto region, Italy, during a three-year period (January 1, 2019 - December 31, 2021). Methods: A list of OMP (n=60) was assembled for the study purposes, according to extensive criteria with regard to the status of orphan designation and of national reimbursement decisions. Results: OMP prescriptions involved 1,010 patients, corresponding to the 2.3% of all the patients monitored by the RD registry. Nearly one out of five (22.8%) was a pediatric patient at the time of the first prescription. OMP use interested a limited proportion (17.5%) of diseases approaching the rarity threshold, having a prevalence of less than five per 10,000, whilst individuals affected by these more common rare conditions represented the 49% of all the patients receiving an OMP prescription. A clustering effect of OMP use was observed in selected groups of diseases, mainly neurological, hematological and hereditary metabolic ones. Medication plans including an OMP present in the 45.9% of the cases a high level of complexity, both in terms of nature and number of co-prescribed treatments. Off-label use interested the 15.3% (n=155) of all the RD patients with at least an OMP prescription during the study period. Conclusions: Data collected in a real-world setting through population-based registries globally monitoring RD patients, including related medication plans, have the potential to identify which diseases, and thus patients, have less benefit from the advent of OMP so far. Furthermore, in the rapidly evolving RD therapeutic landscape, they can help understand which therapeutic areas are most in need of investment to address existing unmet care needs.